2020
DOI: 10.1016/j.ejvs.2020.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair for Retrograde Type A Intramural Haematoma with Intimal Tear in the Descending Thoracic Aorta

Abstract: WHAT THIS PAPER ADDS This is the first report with mid term follow up on endovascular thoracic aortic repair for patients with acute retrograde type A intramural haematoma with intimal tear in the descending thoracic aorta. It now includes 18 patients from four institutions and demonstrates that thoracic endovascular aneurysm repair is feasible and a promising alternative for the treatment of this complex type of pathology Objective: The current treatment for acute retrograde type A intramural haematoma (IMH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…By contrast, the effect of TEVAR for re-TAIMH was more striking. In previous studies with a total number of 37 patients, there was no in-hospital mortality, and two patients died in the follow-up of 24 months, of which a cohort including 18 patients achieved 100% overall survival rate and favorable remolding during 28.7 ± 18.9 months (7,8,10,19,23). However, the inadequacy of the sample size reduced the persuasiveness of these studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…By contrast, the effect of TEVAR for re-TAIMH was more striking. In previous studies with a total number of 37 patients, there was no in-hospital mortality, and two patients died in the follow-up of 24 months, of which a cohort including 18 patients achieved 100% overall survival rate and favorable remolding during 28.7 ± 18.9 months (7,8,10,19,23). However, the inadequacy of the sample size reduced the persuasiveness of these studies.…”
Section: Discussionmentioning
confidence: 95%
“…Re-TAIMH was currently a relatively obscure concept that TAIMH accompanied by PAU or ULP in descending aorta or type B AD was all included (7)(8)(9)(10)12). In recent years, the small tear or rupture of the intima was found in CTA and was confirmed during the operation within some patients with IMH (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their outcomes were satisfactory, with the hematoma in ascending aorta completely reabsorbed in all the 8 patients. And very recently, Ryoi et al reported their experience with TEVAR for a series of 18 cases of retrograde type A IMH, among whom 11 presented aortic dissection and 7 presented IMH in descending aorta (11). Another group, Li et al reported TEVAR for 15 cases with type B aortic dissection associated with retrograde type A IMH (27).…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic endovascular aortic repair (TEVAR) is a less invasive alternative and its value for descending thoracic aortic diseases has been well confirmed (8). And recently several studies have reported the application of TEVAR in retrograde type A IMH or aortic dissection or IMH to exclude the intimal tear in descending aorta (9)(10)(11). TEVAR could be a possible treatment strategy for patients with retrograde type A IMH, but its safety and efficacy are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%